PERBANDINGAN BENTUK TINDAK TUTUR MEMINTA OLEH PEMBELAJAR BIPA DARI KOREA DAN PENUTUR ASLI BAHASA INDONESIA: KAJIAN BAHASA ANTARA - Adista Nur Primantari; I Dewa Putu Wijana (Universitas Muhammadiyah Surakarta, 2016)
This study is aimed at comparing the form of request utterances in bahasaIndonesia produced by Korean learners of Indonesian with the native speakers.Data in this research were collected through a direct fieldwork by recordingand taking notes on conversations produced by Korean learners of Indonesianin Yogyakarta. After collecting the data, we analyze them through comparisonof the data between the Korean and Indonesian speakers. It turns out thatthe Korean learners of Indonesian produce different request utterance formscompared to the native speakers. The patterns of the request utterances can beseen in three different forms: the structure, the variation, and the strategy of theutterances. The difference between utterances produced by the learners and thenative speakers found in the choice of formal and informal styles, strategy ofrequest, semantic formulas, and personal pronouns.